A polarisation-independent blue-phase liquid crystal microlens using an optically hidden dielectric structure. Issue 4 (16th March 2017) - Cui, Jian-Peng; Fan, Hao-Xiang; Wang, Qiong-Hua
ABSTRACT: A polarisation-independent blue-phase liquid crystal microlens using an optically hidden dielectric structure is proposed. In this design, the non-uniform electric field across the lens aperture is obtained by the modulation of the effective dielectric constant of an optical hidden layer. As the applied voltage varies from 0 to 150Vrms, the focal length of the lens can be tuned from ∞ to 16.6 mm. Simulation results show that this device has a parabolic-like profile and exhibits polarisation-independent property. Graphical Abstract: